(untitled) (Revista Española de Fisiología, 1990)
Research on kinetic and hormonal features of breast cancer has led to the development of indices which either reflect accurately the prognosis (incorporation of tritium labelled thymidine) or predict the response to hormonal treatment (presence and concentration of estrogen and progesterone receptors). However, the relationship between cellular proliferation and tumour hormono-dependence has been little studied so far. We describe this relationship in the hormone-dependent MCF-7 cell line cultured in monolayers in MEM + 10% FCS or MEM + 10% FCS (s). We have found that: 1) cellular proliferation and estrogen or progesterone receptor concentration were mutually dependent, the greatest estradiol binding capacity was obtained in cells in which mitotic activity had been slowed down (G0/G1) by the antiestrogenic action of hydroxytamoxifen added to the culture; 2) the presence of estradiol in the culture medium induced marked changes in the synthesis and catabolism of estrogen and progesterone receptors; and 3) both receptors acted as functional proteins whose intracellular concentrations varied depending on the phases of the mitotic cycle.